The Impact of Cash Flows and Weighted Average Cost of Capital to Enterprise Value in the Oil and Gas Sector - Pavel, Zhukov (Journal of Reviews on Global Economics, 2018)
This paper investigates whether there is relationship between fluctuations of enterprise value or capitalization and related changes of WACC and cash flows. The study carried on the sample of some companies from the oil and gas sector, for the changes at intermediate term - from a quarter to three years. At the first stage the common model of discounting free cash flow on WACC was considered as the base model for research. The main conclusion was - intermediate term changes in the enterprise value are independent from changes of WACC. Dependence from changes in cash flows is either insignificant, except permanent growth rate for some growing companies. Finally it is concluded, that traditional WACC is not relevant discount rate for an assessment of enterprise value. At the second stage the alternative method for assessment of enterprise value was proposed, where cash flow is considered equal to expected value, which may grow with permanent growth rate. The method is based on stochastic cost of capital, similar to the generalized method of moments proposed by J. Cochrane, but different in conduction.